Physiological reactivity to acute mental stress in essential hypertension—a systematic review - Walther, Lisa-Marie; Wirtz, Petra H. (Frontiers in Cardiovascular Medicine, 2023)
Objective: Exaggerated physiological reactions to acute mental stress (AMS) are associated with hypertension (development) and have been proposed to play an important role in mediating the cardiovascular disease risk with hypertension. A variety of studies compared physiological reactivity to AMS between essential hypertensive (HT) and normotensive individuals (NT). However, a systematic review of studies across stress-reactive physiological systems including intermediate biological risk factors for cardiovascular diseases is lacking.Methods: We conducted a systematic literature search (PubMed) in November and December 2022 for original articles and short-reports, published in English language in peer-reviewed journals. We targeted studies comparing the reactivity between essential HT and NT to AMS in terms of cognitive tasks, public speaking tasks, or the combination of both, in at least one of the predefined stressreactive physiological systems.Results: We included a total of 58 publications. The majority of studies investigated physiological reactivity to mental stressors of mild or moderate intensity. Whereas HT seem to exhibit increased reactivity in response to mild or moderate AMS only under certain conditions (i.e., in response to mild mental stressors with specific characteristics, in an early hyperkinetic stage of HT, or with respect to certain stress systems), increased physiological reactivity in HT as compared to NT to AMS of strong intensity was observed across all investigated stress-reactive physiological systems. Conclusion: Overall, this systematic review supports the proposed and expected generalized physiological hyperreactivity to AMS with essential hypertension, in particular to strong mental stress. Moreover, we discuss potential underlying mechanisms and highlight open questions for future research of importance for the comprehensive understanding of the observed hyperreactivity to AMS in essential hypertension.